Earthquake fear and flourishing: serial mediation of meaningful living and psychological adjustment - Okur, Sinan; Karaagac, Zahide Gul; Yilmaz, Fatma Betul; Kutuk, Hasan; Satici, Seydi Ahmet (TAYLOR & FRANCIS LTD, 2025)
The earthquake fear seriously influences the psychological wellbeing of individuals. It is necessary to explain in more detail the nature of the link between earthquake fear and flourishing. In this context, the purpose of this study is to examine the serial mediator role of meaningful living and psychological adjustment in the relationship between earthquake fear and flourishing. The sample consisted of 401 individuals (81.8% females, Mage = 24.36, SD = 5.30). Participants completed four scales measuring earthquake fear, flourishing, meaningful living, and psychological adjustment. The results of the correlation analysis demonstrated significant relationships between these variables. In addition, structural equation modelling revealed that meaningful living and psychological adjustment have a serial mediating role in the relationship between earthquake fear and flourishing. These findings prove the relationship between earthquake fear and mental health.
Keywords: Flourishing; earthquake fear; meaningful living; psychological adjustment; serial mediation analysis; LIFE SATISFACTION; Environmental Sciences & Ecology